La matemática en el razonamiento lógico de los niños y niñas de los sextos y séptimos años de educación básica de la Escuela Ramón Moncayo Benítez de la parroquia Bombolí, cantón Santo Domingo, provincia Santo Domingo de los Tsáchilas, durante el periodo 2009 - 2010 - Camacho Llanos, Jorge Cervantes (2010)
This work isorganized from this topic: “Mathematics in the logical reasoning of the children of sixth and seventhyears of basiceducation of the school Ramón Moncayo Benítez, during the school year2009 - 2010. This work is based on the next question: Does Mathematics influence in the development of the logical reasoning of the children of sixth and seventh years of basic education of the school Ramón Moncayo Benítez ? This research problem is justified taking in mind the need of giving a systematic treatment which will permit to give real solutions to the present problem. Also, It describes as a problem to join the Theory and the practice, which is faced daily with the students. In order to get the structure of the work, we get general and specific objectives, It arises the hypothesis on which we can get the two variables: dependant and independent . After that we made “El Marco Teórico” which refers to the following aspects: Scientific, Conceptual, Legal and Referential. The Methodological design shows the strategies of the research; the instruments needed for the data collection and how to process them. Chapter III refers to the analysis and data which were gotten and organized previously according to the rule of Statistics. After processing this information, we established the following conclusions and recommendations, as a result of this research we have got the proposal of elaborating a manual of active and new Methodological Strategies of Mathematics which will be very useful for the development of the logical reasoning.